PENYULUHAN TENTANG GEJALA LONG COVID BAGI PETUGAS KESEHATAN DI KLINIK ATLANTIS KOMPLEKS MMTC DELI SERDANG - Saiful Batubara; Julahir Hotmatua Siregar (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The symptoms of the COVID-19 disease are not only experienced by patients when they are infected with the virus, but some case report data shows that the Long Covid phenomenon is experienced by patients who have been declared cured. Most of the patients who experience the Long Covid phenomenon are classified as mild to moderate symptoms. The cause of the occurrence of Long Covid is still being investigated further, but there is a hypothesis that long covid occurs due to organ damage due to viruses and residual inflammation that continues even though the virus is not there. The most common symptoms of Long Covid are fatigue, shortness of breath, cough, joint pain, chest pain, including disturbances of smell and taste. From the counseling carried out for health workers at the Atlantis Clinic, results were obtained in the form of a significant increase in knowledge and reducing the gap in knowledge between participants in the field of life related to the symptoms of SARS-CoV-2.